Neutral Nonenzymatic Glucose Biosensors Based on Electrochemically Deposited Pt/Au Nanoalloy Electrodes - Lin FY (Dove Medical Press, 2021)
Fang-Yu Lin,1 Pei-Yuan Lee,1,2 Tien-Fu Chu,3 Chang-I Peng,3 Gou-Jen Wang1,3,4 1Graduate Institute of Biomedical Engineering, National Chung-Hsing University, Taichung, 40227, Taiwan; 2Department of Orthopedics, Show Chwan Memorial Hospital, Changhua, 50008, Taiwan; 3Department of Mechanical Engineering, National Chung-Hsing University, Taichung, 40227, Taiwan; 4Regenerative Medicine and Cell Therapy Research Center, Kaohsiung Medical University, Kaohsiung, 80708, TaiwanCorrespondence: Gou-Jen Wang Email gjwang@dragon.nchu.edu.twBackground: Type I diabetes occurs when the pancreas can only make limited or minimal insulin. Patients with type 1 diabetes need effective approaches to manage diabetes and maintain their blood-glucose concentration. Recently, continuous glucose monitoring (CGM) has been used to help control blood-glucose levels in patients with type 1 diabetes. Patients with type 2 diabetes may also benefit from CGM on multiple insulin injections, basal insulin, or sulfonylureas. Enzyme-free glucose detection in a neutral environment is the recent development trend of CGM.Materials and Methods: Pt/Au alloy electrodes for enzyme-free glucose detection in a neutral environment were formed by electrochemically depositing Pt/Au alloy on a thin polycarbonate (PC) membrane surface with a uniformly distributed micro-hemisphere array. The PC membranes were fabricated using semiconductor microelectromechanical manufacturing processes, precision micro-molding, and hot embossing. Amperometry was used to measure the glucose concentration in PBS (pH 7.4) and artificial human serum.Results: The Pt/Au nanoalloy electrode had excellent specificity for glucose detection, according to the experimental results. The device had a sensitivity of 2.82 μA mM− 1 cm− 2, a linear range of 1.39– 13.9 mM, and a detection limit of 0.482 mM. Even though the complex interfering species in human blood can degrade the sensing signal, further experiments conducted in artificial serum confirmed the feasibility of the proposed Pt/Au nanoalloy electrode in clinical applications.Conclusion: The proposed Pt/Au nanoalloy electrode can catalyze glucose reactions in neutral solutions with enhancing sensing performance by the synergistic effect of bimetallic materials and increasing detection surface area. This novel glucose biosensor has advantages, such as technology foresight, good detection performance, and high mass production feasibility. Thus, the proposed neutral nonenzymatic glucose sensor can be further used in CGMs.Keywords: neutral nonenzymatic glucose biosensor, Pt/Au nanoalloy electrode, electrochemical deposition, synergistic effect